Efecto de la aplicación de cuatro dosis de n, p, k y mg, en el cultivo de Palma Aceitera (Elaeis Guineensis Jacq), realizado en el vivero de la empresa Palmas del Shanusi S.A - Pinedo Dávila, Alex (2013)
The present investigation entitled "Effect of the application of four doses of N, P, K and Mg in the cultivation of oil palm (Elaeis guineensis Jacq) conducted in the nursery of the company Palms Shanusi SA", executed in the company in question, whose objectives were to: 1) evaluate the effect of the application of four doses of N, P, K and Mg in the vegetative development of seedlings of oil palm (Elaeis guineensis Jacq) under nursery conditions between the months of June 2008 to April 2009, the company developed in Palmas del Shanusi SA 2) Reduce production costs demanded by the manual application of fertilizers in the cultivation of oil palm (Elaeis guineensis Jacq) under nursery conditions. 3) Conduct economic analysis of the production of seedlings of oil palm (Elaeis guineensis Jacq) under nursery conditions. The experimental design was a randomized complete block (RCBD) with four repetitions and four treatments per replicate, for T0 (15N-15P-6K-4mg), T1 (less than 10 % of T0), T2 (less 20 % of T0), T3 (less than 30 % of T0), using 12 experimental units per treatment, planting distance was 0, 70 m between rows and 0, 60 m between plants respectively. The T0 (15N-15P-6K-4mg) and T1 (less than 10 % of T0), obtained higher net revenues to S /. 173 193, 12 and S /. 167 085, 98 respectively, this is a consequence of the increase in fertilizer doses to the different treatments, which represents higher costs in production, but with good quality seedlings. The B / C obtained results between 1, 41 to 1, 58 which corresponds to T2 (less 20 % of T0) and T0 (15N-15P-6K- 4mg), respectively. These results represent optimal values in profitability.